Enhanced stress corrosion cracking resistance and electrical conductivity of a T761 treated Al-Zn-Mg-Cu alloy thin plate. (23rd January 2018) - Chen, Xu; Zhai, Sudan; Gao, Di; Liu, Ye; Xu, Jing; Liu, Yang
Abstract: The stress corrosion cracking (SCC) behavior, electrical conductivity and mechanical properties of an Al-Zn-Mg-Cu alloy pre-stretched thin plate for wing skin were researched in this paper. The microstructures and SCC fracture surfaces of the alloy treated at different conditions were characterized by transmission electron microscopy, optical microscopy and scanning electron microscopy. Results indicated that with the increasing of aging temperature, the electrical conductivity and the elongation increased greatly, while the strength decreased gradually which were closely associated with the type and morphology of the precipitates. Compared with the T6 treated alloy, the SCC resistance of the T761 treated Al-Zn-Mg-Cu alloy was improved greatly. The SCC behavior of the T6 treated alloy was dominated by anodic dissolution theory, whereas the hydrogen induced cracking controlled the fracture behavior of the T761 treated alloy which was influenced by the morphology of grain boundary precipitates in this investigated alloy.